Beyond the enclave : towards a pro-poor and inclusive development strategy for Zimbabwe - Kanyenze, Godfrey (Weaver Press in association with Alternatives to Neo-liberalism in Southern Africa, Labour & Economic Development Research Institute, Zimbabwe and the Zimbabwe Congress of Trade Unions, 2011)
Beyond the Enclave sets out to unravel the contradiction of a country, Zimbabwe, where a rich, diverse resource base co-exists with endemic poverty. One reason lies in the colonial economy, which was predicated on an ideology of white supremacy, creating an enclave formal economy employing one-fifth of the labour force. Yet over three decades after independence, the non-formal segment has become even more entrenched. This book assesses Zimbabwe's economy through three main phases: 1980- 0 when a strong social policy framework proved difficult to sustain due to erratic growth, and 1991- 6, when "structural adjustment" demanded a market-driven approach to development. The third phase is characterized by crisis-management leading to policy inconsistencies and reversals. Not surprisingly, such incoherence saw the economy descend into hyperinflation and paralysis in 2007- 8, leading to the signing of the Global Political Agreement in September 2008. In the absence of formal dollarization, economic recovery after the adoption of the multi-currency regime has remained fragile, leaving an estimated 70 per cent of the population outside the banking system. This has further entrenched uneven (enclave) growth as the economy remains locked in a low-income poverty trap. There is a need to facilitate transition towards formality to promote decent jobs. Furthermore, a strategic, developmental role for the state in the economy is now widely recognized as vital for development. Beyond the Enclave argues for a new approach to development in Zimbabwe based on pro-poor and inclusive strategies, which will contribute to the well-being of all of its citizens and wise stewardship of its resources. It offers suggestions on policy formulation, implementation, monitoring and evaluation in all sectors, designed to promote inclusive growth and humane development